Kapal ng Mukha, Kapalpakan, at Iba Pang Salik ng Kabibuhan - Capinding, Ronan B (Archīum Ateneo, 2020)
In this lecture, Sir Ron observes how students become more guarded and lose enthusiasm in learning Filipino as they reach higher grade levels. He then explores how this is connected to fear of failure, shame, and suggests how teachers can approach this problem. Speaker: Ronan B Capinding currently teaches Filipino in the Ateneo High School, and was formerly the Associate Principal for Student Affairs and Formation at the Ateneo Junior High School. He also teaches Acting and Directing in the Fine Arts Department of the Loyola Schools, and Leadership and Corporate Creativity in Ateneo Center for Continuing Education. Aside from teaching, he is also an actor, director, dialogue coach, choreographer, playwright and Filipino translator. He has received awards such as Best Actor by the Galian ng Sining at Kultura, Outstanding Original Script in the 2012 Gawad-Buhay Awards, and Aliw Awards' Best Non-Musical Production in 2015. He is the author of the book "Ikaw at ang Kawili-wiling Wika" and the founder of Ateneo High School Organizations Teatro Baguntao and IndAK. He has a Masters Degree in Educational Administration from the Ateneo de Manila University.